Critical success factors & risks in property investment in China - Lim, Soon Kam; Adul Hamid, Razali (Faculty of Built Environment, 2001)
This paper attempts to provide some insights toward critical success factors, risks encountered and suggestions by foreign investors in property investment in Xiamen (Special Economic Zone), China. The economic prospects of Xiamen as a whole were introduced. The objectives of the study and methodology used were then described, followed by the explanation of data collection and data analysis and results derived thereof were discussed, coupled with related statistics and suggestions by respondents. As a result, this paper has come out with a list of factors and risks affecting the success of property investment from the foreign investors' perspectives in Xiamen, China